2021
DOI: 10.1007/s11664-021-09199-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical and Magnetic Properties of Diamagnetic Cd2+ Incorporated Cobalt Ferrite Thin Films Deposited by Spray Pyrolysis

Abstract: Cadmium (Cd 2+ )-substituted cobalt ferrite thin films with configuration Co 1−x Cd x Fe 2 O 4 (x = 0.0 to 1.0 in steps of 0.2) were grown via spray pyrolysis. The influence of Cd 2+ substitution on structural and functional properties was investigated. X-ray diffraction analysis clearly shows a single-phase cubic spinel geometry (Fd3m space group). The ultrafine nanocrystallites with average crystallite dimensions of 11-15 nm were obtained. The surface topography was inspected by scanning electron microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The coercivity also decreased with increase in Cr 3+ content. Zengpeng Li et al, [71] synthesized chromium substituted cobalt ferrite hollow nanotubes. X-ray analysis confirmed that formation of spinel structure with phase purity.…”
Section: Cr Substitutionmentioning
confidence: 99%
“…The coercivity also decreased with increase in Cr 3+ content. Zengpeng Li et al, [71] synthesized chromium substituted cobalt ferrite hollow nanotubes. X-ray analysis confirmed that formation of spinel structure with phase purity.…”
Section: Cr Substitutionmentioning
confidence: 99%